Brain transmitter precursors and metabolites in diabetic ketoacidosis. Issue 6 (June 1982) - Curzon, G; Kantamaneni, B D; Callaghan, N; Sullivan, P A
Abstract : Patients studied during recovery from an episode of ketoacidotic diabetes had raised blood glucose, plasma free fatty acid and plasma free tryptophan concentrations. Plasma total tryptophan was decreased. Well controlled diabetics showed normal values. The ketoacidotic patients had increased lumbar CSF tryptophan and 5-hydroxyindoleacetic acid concentrations. Plasma tyrosine and CSF tyrosine and homovanillic acid concentrations were normal in both diabetic groups. The results are discussed in relation to somewhat similar findings in uraemic and hepatic encephalopathy and to changes in rats with streptozotocin diabetes.